Modeling of heat exchanger in the closed system of mirror and diffusion surfaces - Бабак, В. П.; Ковтун, С. І.; Хайдуров, В. В.; Щербак, Л. М. (Science-based technologies, 2018)
The paper presents the results of mathematical and computer simulation of the process of energy transfer by radiation in a closed system consisting of diffuse and specularly reflecting surfaces. The distribution of local values of the surface density of the heat flux over the surface of the heat removal is obtained, which made it possible to estimate the uniformity of the distribution of the heat flux field. The resolving view factor for a given system is also determined, depending on the geometric dimensions of the radiator. Using the software modeling package, the share of each type of heat transfer in the total heat flux is estimated. Based on the results of a numerical calculation of the total normal heat flux, the determining role of the radiative component of heat transfer in the process of heat transfer in the closed system under consideration is established.